Computing Cyclically-Adjusted Balances and Automatic Stabilizers - Fedelino, Annalisa (Technical Notes and Manuals; Technical Notes and Manuals ;, 2009)
This technical note focuses on computing cyclically adjusted balances and automatic stabilizers. The note provides guidance on how to decompose overall fiscal balances into cyclical and cyclically adjusted components, and how to interpret automatic fiscal stabilizers. These indicators are commonly used to assess how fiscal policy responds to macroeconomic conditions. Various approaches to cyclical adjustment and estimation of the automatic stabilizers are possible. This note focuses on the approach used by the IMF's Fiscal Affairs Department in the paper on the State of Public Finances and in the Fiscal Monitor.